Principal Components Analysis the Biochemical Compounds Extracted from Dates Using Three Mixture Design and Identification by GC-MS - Taffaha. A. Arhouma; M. S. Hassan (International Journal of Science and Research (IJSR), 2024)
International Journal of Science and Research (IJSR) Volume 5 Issue 4, April 2016